Elementy perturbacyjne gospodarstwa domowego dla rozwoju rodziny - Paradysz, Jan (Wydział Prawa i Administracji UAM, 1977)
The Author deals with the group of perturbation elements the preceding appearance of which diminishes the probability of the succesive demographic phenomena; that probability however, does not fall to zero. The group of perturbative elements consists i.a. of the economic decision making of the family. The research on the procreative decisions of the married couples (marriages contracted in 1955-1959), resident in the former voivodeship of Rzeszów up to 31 XII 1973, has brought the following results: The purchase of durable goods perturbed the first live birth to a little extent. But the second live birth succeeded purchase of various durable goods. In the light of the applied entropy analysis the probabilities of live births were much more concentrated at the model value than those of the purchase of rather common durable goods. The choice of the first live birth is mostly defined, especially in the rural areas where the real entropy amounted to 53,9% of the maximal entropy (table 4). In the case of successive live births the uncessive live births the unspecified choice increases.
Household perturbative elements in increasing the family